TAXPAYER COMPLIANCE AFTER USING THE TAPPING BOX ACCORDING TO LOCAL REGULATION: A Study at Hotel 61 Banda Aceh - Zuhra, Ulfia; Nahara Eriyanti (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
Implementing the Tapping box as a transaction recording device on hotel tax is one of the efforts to modernise local tax administration to improve transparency and accuracy of tax reporting. This study aims to determine taxpayer compliance with Mayor Regulation No. 21 of 2020 on the hotel business in the city of Banda Aceh. The research method used is empirical juridical research, through a qualitative approach with data collection techniques through direct observation, interviews with managers of 61 hotels in the city of Banda Aceh and officers of the Banda Aceh City Financial Management Agency, and documentation related to the application of tapping boxes. The results showed that applying the Tapping box significantly increased hotel taxpayer compliance in reporting and paying taxes, because this tool minimizes turnover reporting fraud and facilitates local government supervision. In addition, tax compliance is also influenced by taxpayer awareness and the existence of administrative sanctions for those who refuse to install Tapping boxes. Thus, using Tapping boxes effectively increases hotel tax compliance and optimizes local tax revenue in Banda Aceh City.